Non-triggered sequential-release liposomes enhance anti-breast cancer efficacy of STS and celastrol-based microemulsion 1. (22nd October 2018) - Qu, Ding; Wang, Lixiang; Qin, Yue; Guo, Mengfei; Guo, Jian; Huang, Mengmeng; Liu, Yuping; Liu, Congyan; Li, Hui; Chen, Yan
Abstract : A codelivery system that sequentially releases its contents is an effective strategy to enhance anticancer efficacy. Abstract : A codelivery system that sequentially releases its contents is an effective strategy to enhance anticancer efficacy. Here, we fabricated multicomponent-based liposomes (T/CM-L) loaded with sodium tanshinone IIA sulfonate (STS) and a small-sized microemulsion of celastrol (CM), which shows synergistic anti-breast cancer activity through the initial release of STS for modulation of the tumor microenvironment, and subsequent release of CM (and its payloads) for eradication of tumor tissues. In vitro studies exhibited that T/CM-L induced massive apoptosis of MCF-7 cells, indicating a coordinated cytotoxicity against cancer cells. Once the liposomes had accumulated at the tumor site, STS was released from T/CM-L in the first place to repair abnormal vessels as well as to decrease the level of fibroblasts. Owing to the barriers of the microemulsion and the liposomes, the celastrol was then unloaded at a moderate rate to kill the tumor cells, which resulted in the shrinkage of the tumor size. Furthermore, T/CM-L displayed diminished systemic toxicity compared to celastrol used alone. Our work offers a novel strategy for combination anticancer treatment and holds promising potential not only for breast cancer treatment, but also for the treatment of other solid tumors.